High price premiums as barriers to organic meat demand? A hedonic analysis considering species, cut and retail outlet - Matthias Staudigel; Aleksej Trubnikov (Australian Journal of Agricultural and Resource Economics, 2022)
Rigid price setting and high organic price premiums have been perceived as major purchase barriers to organic meat products. While emerging price and product differentiation have been reported for organic products in other categories, empirical evidence for the organic fresh meat market is lacking. We estimate a hedonic pricing model based on German household scanner data for fresh red meat and poultry purchases from 2012 to 2014. We derive and test for differences in organic price premiums across distribution channels, species and product type. Our results indicate significant variation in organic premiums, which range from 14 per cent for minced beef to 108 per cent for chicken breasts, and are considerably lower than previously reported estimates. We also find substantial overlaps in the distributions of conventional and organic prices for selected products. Our results suggest that high price premiums can no longer serve as the dominant explanation for low market shares of organic red meat. Marketers and policymakers may instead communicate the benefits of organic meat over conventional premium alternatives more clearly or increase the availability of organic meat.
Keywords: 330; Germany; hedonic analysis; household scanner data; meat; organic; price premiums